Bryher: Two Novels Development and Two Selves - Horrigan, Patrick E. (University of Wisconsin Press, 2000)
Bryher (born Annie Winifred Ellerman) is perhaps best known today as the lifelong partner of the poet H.D. She was, however, a central figure in modernist and avant-garde cultural experimentation in the early twentieth century; a prolific producer of poetry, novels, autobiography, and criticism; and an intimate and patron of such modernist artists as Gertrude Stein, Marianne Moore, and Dorothy Richardson. Bryher's own path-breaking writing has remained largely neglected, long out of print, and inaccessible to those interested in her oeuvre. Now, for the first time since their original publication in the early 1920s, two of Bryher's pioneering works of fictionalized autobiography, titled Development and Two Selves, are reprinted in one volume for a new audience of readers, scholars, and critics.